2002
DOI: 10.1111/j.1741-3729.2002.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maternal Beliefs in Predicting Home Learning Activities in Head Start Families*

Abstract: A conceptual model specifying that maternal beliefs (maternal self-efficacy, perceived control) mediate the relation between childfamily characteristics (child's difficult temperament, mother's education, stressful life events) and the extent of involvement in home learning activities in Head Start families was tested. The sample was 306 mothers (51% Mexican American, 36% Anglo American, 13% other minorities). Results provided partial support for the model (i.e., parental self-efficacy mediated the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 54 publications
2
31
0
9
Order By: Relevance
“…Furthermore, the demonstration of parental motivational beliefs as mediators of the relation between parenting stress and family involvement adds to the literature by explaining a process predicting family involvement. The study also expands the results of similar work by Machida et al (2002) who found that parent efficacy mediated the effect of family stress on mothers' reports of family involvement in home learning activities for a population of children without disruptive behaviors.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, the demonstration of parental motivational beliefs as mediators of the relation between parenting stress and family involvement adds to the literature by explaining a process predicting family involvement. The study also expands the results of similar work by Machida et al (2002) who found that parent efficacy mediated the effect of family stress on mothers' reports of family involvement in home learning activities for a population of children without disruptive behaviors.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, parents who view themselves as less able to effectively contribute to their child's education are more likely to refrain from participating in such activities. Parent efficacy has also been found to partially mediate the effect of children's difficult temperament and family stress on mothers' reports of family involvement in home learning activities (Machida, Taylor, & Kim, 2002). That is, family stress may indirectly and negatively influence family involvement through lowered parent efficacy.…”
Section: Parent Efficacymentioning
confidence: 96%
“…High parental self-efficacy is correlated with competent parenting behaviour and positive parenting practices (Jones & Prinz, 2005;Machida, Taylor & Kim, 2002) and is known to play an important role in parents' psychological functioning. It is inversely related to both maternal depression (Cutrona & Troutman, 1986;Teti & Gelfand, 1991) and parental stress (Gross, Fogg & Tucker, 2005;Scheel & Rieckmann, 1998) and there is further evidence that it is positively associated with role satisfaction (Coleman & Karraker, 2000) and influenced by the parents' personal characteristics (Sevigny & Loutzenhiser, 2009).…”
Section: Parental Self-efficacymentioning
confidence: 99%
“…These naively confident mothers, as Davis suggested (1989), were identified as those who might experience difficulties being involved in intervention programs because they would question very little about their parenting and remain unaware of their childrenÕs developmental needs. On the other hand, a recent study conducted by Machida et al (2002) found maternal self-efficacy was significantly related to parental involvement in home learning activities in a sample of Head Start families. In addition, with a sample of Korean working mothers of infants living in poverty, significant differences were detected between the two subgroups by SES (on welfare vs. not on welfare) in maternal self-efficacy (Seo, 2006).…”
Section: Introductionmentioning
confidence: 90%
“…The mothers living in poverty tended to report that they perceived more confidence in parenting than the mothers with higher SES (Seo, 2006). Those two recent studies (Machida et al, 2002;Seo, 2006) did not include the variable of maternal knowledge of infant development in the equations of interest. There might be biases that may serve as defense for the mothers' ego in judging their levels of maternal self-efficacy (Conrad et al, 1992;Seo, 2006), or there might be other important covariates unexplained.…”
Section: Introductionmentioning
confidence: 96%